Dewatering of Kerosene using Hydrocyclone (Journal of Engineering, 2020)
Water/oil emulsion is considered as the most refractory mixture to separate because of the interference of the two immiscible liquids, water and oil. This research presents a study of dewatering of water / kerosene emulsion using hydrocyclone. The effects of factors such as: feed flow rate (3, 5, 7, 9, and 11 L/min), inlet water concentration of the emulsion (5%, 7.5%, 10%, 12.5%, and 15% by volume), and split ratio (0.1, 0.3, 0.5, 0.7, and 0.9) on the separation efficiency and pressure drop were studied. Dimensional analysis using Pi theorem was applied for the first time to model the hydrocyclone based on the experimental data. It was shown that the maximum separation efficiency; at split ratio 0.1, was 94.3% at 10% concentration and 11 L/min flow rate; at 0.3 split ratio, was 70.8% at 10% concentration and 11 L/min flow rate; at split ratio 0.5, was 82.1% at 12.5% concentration and 11 L/min flow rate; at split ratio 0.7, was 70% at 11 L/min, for 5%, 7.5%, and 12.5% concentrations; at 0.9 split ratio was 96.8% at 11 L/min flow rate and 5% concentration. The maximum separation obtained within these ranges of variables was 96.8% at 0.9 split ratio, 11 L/min flow rate and 5% concentration. The maximum pressure drop recorded was 3.6 bar at split ratio 0.1 and 11 L/min flow rate for all concentrations. The correlations obtained by the dimensional analysis were;  at split ratio 0.1,  at split ratio 0.3,  at split ratio 0.5,   at split ratio 0.7, and  at split ratio 0.9. As an average  for all the studied variables.